-33=-8g+7

Simple and best practice solution for -33=-8g+7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -33=-8g+7 equation:



-33=-8g+7
We move all terms to the left:
-33-(-8g+7)=0
We get rid of parentheses
8g-7-33=0
We add all the numbers together, and all the variables
8g-40=0
We move all terms containing g to the left, all other terms to the right
8g=40
g=40/8
g=5

See similar equations:

| 3r2+14r+16=0 | | (X)(x+7)=170 | | -2x+4+4x-1=15 | | 84n^2+90n^2=0 | | y/4-4=4 | | 21/28=9/x | | 7n2+13n+6=0 | | 3/2(x-6)=3 | | |x-9|=6 | | 2(x+5)+3x=3x+20 | | v2-9v+14=0 | | 3x+5=5x–1 | | 3m=8m–110 | | 16x^2-34x+16=0 | | 4/5t=75/32 | | Y=2x^2+9x+1 | | (30×x)÷4=48 | | -6y-34=-2(y+9) | | 5x-1=1/2x+18 | | -c/2-3=24 | | 8=-18+3/8-(16-40n) | | -5x+10-4x=-17 | | 2/5-7=12/5x-2x+3 | | 65+(11x−17)=180 | | x-2/8=9 | | 5p+5+5=-2+7p | | n​2​​=2.25 | | (2x-20)=90 | | 90+y=110 | | z+2/3=3 | | .6(-5x+6)+11x=-(-2x+3) | | 0,4(x+5)=0,5(3-x)=2,5 |

Equations solver categories